2018
DOI: 10.1080/00268976.2018.1495849
|View full text |Cite
|
Sign up to set email alerts
|

Kohn–Sham energy decomposition for molecules in a magnetic field

Abstract: I joined the Oslo group of theoretical chemistry in my last semester as a bachelor student. Then, I got my master's degree with Trygve Helgaker and Erik Tellgren as my supervisors, and now, finally, my Ph.D. As such, I've been a part of this excellent community for nine years. I've seen the Centre of Theoretical and Computational Chemistry end, and I've seen the Hylleraas Centre of Quantum Molecular Sciences rise. Naming all the generous, kind and interesting people I've interacted with over the years is impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…In general, when an external magnetic field is applied to a molecule, the energy may either decrease paramagnetically or increase diamagnetically. Paramagnetism is often (though not always 73 ) associated with open-shell molecules, whilst diamagnetism is associated with closed-shells. The electronic Hamiltonian in the presence of a uniform magnetic field B is …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, when an external magnetic field is applied to a molecule, the energy may either decrease paramagnetically or increase diamagnetically. Paramagnetism is often (though not always 73 ) associated with open-shell molecules, whilst diamagnetism is associated with closed-shells. The electronic Hamiltonian in the presence of a uniform magnetic field B is …”
Section: Resultsmentioning
confidence: 99%
“…This in turn enables the calculation of excitation energies rigorously at the meta-GGA level in line with ref ( 52 ) at zero field and seamlessly for magnetic fields of arbitrary strengths. Our previous work has demonstrated that, in such strong magnetic fields, the use of meta-GGA functionals including current-dependent terms can deliver much improved accuracy compared with LDA and GGA type functionals 47 , 73 and so provide a good starting point for the determination of excitation energies in strong magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…Basis set convergence of the anapole susceptibility values was well-studied and MODENA basis sets were proposed to be superior to Dunning's basis sets. Previous studies of density functional approximations for magnetic properties like magnetizabilities and NMR shielding constants 12,35,36 have indicated that meta-GGA functionals, in particular cTPSS, are promising candidates for capturing even exotic magnetic effects very far from the domain these functionals were explicitly constructed for. Remarkably, it was also found that the errors for the paramagnetic closed shell molecules were an order of magnitude higher for all the methods studied except for cTPSS (current TPSS).…”
Section: Introductionmentioning
confidence: 99%
“…Other more specific tools based on the fractional occupation number weighted density, 194 electron localization functions (ELF) 195 or KS energy decomposition 196 have been developed for a qualitative analysis of complicated electronic structure solutions.…”
Section: Quantitative Analysis Toolsmentioning
confidence: 99%